West Africa's moist convective environment as observed by the Atmospheric InfraRed Sounder (AIRS). (16th January 2023) - Osei, Marian Amoakowaah; Ferguson, Craig R.; Quansah, Emmanuel; Padi, Michael; Amekudzi, Leonard K.; Danuor, Sylvester
Abstract: Knowledge of the seasonal positioning of the Intertropical Discontinuity (ITD) is critical to understanding seasonal moist convective processes and associated rainfall over West Africa. This study constitutes a new analysis of the seasonality of moist convection over West Africa, relative to the ITD, based on NASA's Atmospheric Infrared Sounder (AIRS) measurements from 2003 to 2018. Results show that AIRS resolves the seasonal march of the ITD, including its inherent diurnal‐scale variations. AIRS captures the north–south daytime skin temperature dipole around the ITD, with greater relative temperatures to the north, especially during March–August. In the vicinity of the nighttime ITD, AIRS profiles indicate increased instability that is characteristic of nocturnal thunderstorm propagation. For seven Ghana weather stations, we show that AIRS positive moisture and equivalent potential temperature anomalies coincide with observed thunderstorm days. On these thunderstorm days, the mean latitude of the AIRS‐derived ITD is displaced 3°, 0.2°, and 2 ° north of its DJF, MAM, and SON climatological positions, respectively, and 1.2 ° south in JJA. Among four common thunderstorm initiation indices considered, the K‐index is determined to be most skillful. The findings of this study contribute to the Global Challenges Research Fund, African Science for Weather Information and Forecasting Techniques project's mission to build local tropical weather forecasting capacity and capabilities in West Africa. Abstract : This study constitutes a new analysis of the seasonality of moist convection over West Africa, relative to the ITD (dashed lines), based on AIRS measurements from 2003 to 2018. Results showed that, AIRS resolves the seasonal march of the ITD, including its inherent diurnal‐scale variations. On thunderstorm days, the AIRS‐derived ITD is displaced between 0.2 ° and 3 ° north (DJF, MAM and SON) and 1.2 ° south in JJA. The George's K‐index is most skillful for seasonal deep convection prediction.